Risk-aware optimized quickest path computing technique for critical routing services. (October 2021) - Sharma, Ashutosh; Cholda, Piotr; Kumar, Rajiv; Dhiman, Gaurav
Highlights: Characterization of the network for the best optimized path using reliability, delay and capacity. Tuning of the network parameters for the prediction/validation for the best optimized Path, according to a given data flow. Best optimized path is useful to choose most appropriate path directly for mission-critical applications without using routing overhead after tuning rule formulations. Abstract: In this paper, a novel model has been proposed for the computation of optimized path with link reliability, delay and capacity. Algorithms have been proposed for the optimized data path with a single link-weight and it constitutes two main parts: (i) characterization of the network for the best optimized path, and (ii) tuning of the network parameters for the prediction/validation for the Best Optimized Path, according to a given data flow. It also needs very little a priori information during the online computation as the computed optimized path requires less computational overhead as each data flow shall be assigned with a precomputed and optimized link weight. Now, with the help of this optimized link weight one can find the optimum path with respect to both risk and lag-time in an online approach simply by adopting the Dijkstra's algorithm. This approach has been illustrated here in this paper with the help of two different topologies for different values of data flow from single source to single destination. Algorithms have been proposed based on this mathematical model. It also can be observed that proposed algorithms are able to compute the optimized path with having complexity of Dijkstra's algorithm when computer together. This study can be claimed that the proposed algorithms are self-sufficient to provide the risk-aware quickest path routing, even without having any prior information on the path to be allocated. One can easily extend it for the case of many source nodes to the many destination nodes as well as for the software defined networking (SDN) in the future work. Graphical abstract: Image, graphical abstract